Anticoagulant Therapy in End Stage Renal Disease on Hemodialysis: A Comprehensive Systematic Review - Jessica; Utomo (International Medical Journal Corp. Ltd, 2024)
Background: =We aimed to investigate the utilization of AC medications among patients who undergo hemodialysis (HD). We performed a systematic review and meta-analysis of observational studies on AC medications used in HD therapy. Methods: The review adhered to PRISMA 2020 standards and analyzed full-text English literature from 2014 to 2024. It excluded editorials, review papers from the same journal, and submissions lacking a DOI. Literature sources included PubMed, SagePub, SpringerLink, and Google Scholar. Result: After three rounds of screening, five articles directly relevant to the systematic review were selected for full-text reading and analysis. Conclusion: AC medications are given in HD patients with high cardiovascular commorbidities to increase vascular patency and prevent thrombosis. Aspirin and P2Y12 inhibitors (PI) such as clopidogrel are commonly used. AC medications might cause shortened longevity of AV access for HD patients. The benefits of AC therapy for cardiovascular protection needs to be evaluated along with its possible effect on AVG outcomes.